AntimiR-132 Attenuates Myocardial Hypertrophy in an Animal Model of Percutaneous Aortic Constriction - Hinkel, Rabea; Batkai, Sandor; Baehr, Andrea; Bozoglu, Tarik; Straub, Sarah; Borchert, Tobias; Viereck, Janika; Howe, Andrea; Hornaschewitz, Nadja; Oberberger, Lisa; Jurisch, Victoria; Kozlik-Feldmann, Rainer; et al. (Journal of the American College of Cardiology, 2021)
Background: Pathological cardiac hypertrophy is a result of afterload-increasing pathologies including untreated hypertension and aortic stenosis. It features progressive adverse cardiac remodeling, myocardial dysfunction, capillary rarefaction, and interstitial fibrosis often leading to heart failure. Objectives: This study aimed to establish a novel porcine model of pressure-overload–induced heart failure and to determine the effect of inhibition of microribonucleic acid 132 (miR-132) on heart failure development in this model. Methods: This study developed a novel porcine model of percutaneous aortic constriction by implantation of a percutaneous reduction stent in the thoracic aorta, inducing progressive remodeling at day 56 (d56) after pressure-overload induction. In this study, an antisense oligonucleotide specifically inhibiting miR-132 (antimiR-132), was regionally applied via intracoronary injection at d0 (percutaneous transverse aortic constriction induction) and d28. Results: At d56, antimiR-132 treatment diminished cardiomyocyte cross-sectional area (188.9 ± 2.8 vs. 258.4 ± 9.0 μm2 in untreated hypertrophic hearts) and improved global cardiac function (ejection fraction 48.9 ± 1.0% vs. 36.1 ± 1.7% in control hearts). Moreover, at d56 antimiR-132-treated hearts displayed less increase of interstitial fibrosis compared with sham-operated hearts (Δsham 1.8 ± 0.5%) than control hearts (Δsham 10.8 ± 0.6%). Of note, cardiac platelet and endothelial cell adhesion molecule 1+ capillary density was higher in the antimiR-132–treated hearts (647 ± 20 cells/mm2) compared with in the control group (485 ± 23 cells/mm2). Conclusions: The inhibition of miR-132 is a valid strategy in prevention of heart failure progression in hypertrophic heart disease and may be developed as a treatment for heart failure of nonischemic origin.
CRIS-Team Scopus Importer:2023-03-08
Keywords: adverse cardiac remodeling; antimiR-132; cardiac hypertrophy; heart failure; microRNA-132